pottery made by mold (the Ayyubid rains as an example) (Damascus University Journal of Historical Studies, 2023)
This research deals with the methods of making pottery in all its forms, especially pots and tools made by molds.The focus is on rainwater preserved in the Aleppo Museum, most of which date back to the Ayyubid period, with their different shapes and the geometric, vegetal and epigraphic decorations they bear. And to identify the techniques used in its manufacture and the quality of the pottery paste used in it, after checking and descriptive study and comparing the rains with each other, and identifying the points of similarity and points of difference between them.
Keywords: pottery; mold; raindrop